Growth vs. margins destabilizing consequences of giving the stock market what it wants - Aghion, Philippe 1956-; Stein, Jeremy C. 1960- (National Bureau of Economic Research, 2004)
"We develop a multi-tasking model in which a firm can devote its efforts either to increasing sales growth, or to improving per-unit profit margins by, e.g., cutting costs. If the firm's manager is concerned with the current stock price, she will tend to favor the growth strategy at those times when the stock market is paying more attention to performance on the growth dimension. Conversely, it can be rational for the stock market to weight observed growth measures more heavily when it is known that the firm is following a growth strategy. This two-way feedback between firm's business strategies and the market's pricing rule can lead to purely intrinsic fluctuations in sales and output, creating excess volatility in these real variables even in the absence of any external source of shocks"--National Bureau of Economic Research web site.
Keywords: Ökonometrisches Modell; Corporations -- Finance -- Econometric models; Stocks -- Econometric models